2015
DOI: 10.1103/physreve.91.042201
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced rigidity in athermal materials: A unified statistical framework

Abstract: Recent studies of athermal systems such as dry grains and dense, non-Brownian suspensions have shown that shear can lead to solidification through the process of shear jamming in grains and discontinuous shear thickening in suspensions. The similarities observed between these two distinct phenomena suggest that the physical processes leading to shear-induced rigidity in athermal materials are universal. We present a non-equilibrium statistical mechanics model, which exhibits the phenomenology of these shear-dr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…The jamming transition for a granular material separates fluidlike states with zero yield stress from solid-like states that can support finite stress. The past two decades have seen a significant effort directed toward understanding the jamming transition in model granular systems consisting of spherical particles [1,2,3,4,5,6], due both to their relative simplicity and relevance for understanding glasses and suspensions [7,1,8,9,10,11]. However, real world industrial and environmental processes usually involve particles that are not spherical, and recent work has shown that such particles can differ significantly in their geometrical and mechanical properties [12,13,14,15,6,16].…”
Section: Introductionmentioning
confidence: 99%
“…The jamming transition for a granular material separates fluidlike states with zero yield stress from solid-like states that can support finite stress. The past two decades have seen a significant effort directed toward understanding the jamming transition in model granular systems consisting of spherical particles [1,2,3,4,5,6], due both to their relative simplicity and relevance for understanding glasses and suspensions [7,1,8,9,10,11]. However, real world industrial and environmental processes usually involve particles that are not spherical, and recent work has shown that such particles can differ significantly in their geometrical and mechanical properties [12,13,14,15,6,16].…”
Section: Introductionmentioning
confidence: 99%
“…Around this volume fraction, shear has the ability to "jam" or rigidify disordered packings [2,13]. The underpinnings of the mechanism are still under intense debate [14][15][16][17][18][19]. One of the complicating factors is that many of the nontrivial mechanical features are transient phenomena, making them particularly difficult to probe, as they are highly dependent on packing preparation, boundary conditions, and other seemingly insignificant details of the system [7,15].…”
mentioning
confidence: 99%
“…The factors that impact the DST phenomenon have been investigated by many scientists [20][21][22][23][24], as well. These researchers found that the concentration and the shear rate can greatly influence the DST behavior of STFs.…”
Section: Introductionmentioning
confidence: 99%